ST-elevation myocardial infarction, severe cardiogenic shock, and myocarditis secondary to leptospirosis: A rare case report - Coana Sukmagautama; Faizal Muhammad; Ken Zuraida Maharestri; Ihsan Hanif; Risalina Myrtha (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Leptospirosis is a bacterial infection that can lead to several organ dysfunctions. However, cardiac involvements in leptospirosis are uncommon findings. The unknown pathogenesis and association between leptospirosis and cardiac involvements can lead to a diagnostic challenge and case rarity. This study aims to report a diagnosis challenge through physical and laboratory examination of a patient with ST-elevation myocardial infarction (STEMI) and myocarditis without common leptospiral-associated organ dysfunction features. We also report the therapeutic strategies in this case, despite its clinical guideline limitation. Case: A 35-year-old male patient came to the emergency department with flu-like symptoms. Twenty-four hours later, the patient showed acute angina, STEMI, and elevated high-sensitivity cardiac troponin followed by cardiogenic shock without significant modifiable and non-modifiable risk factors for heart diseases. The patient received fibrinolytic, supportive therapy and correction of hemodynamic derangement. We found thrombocytopenia on the second day. Surprisingly, the immunoserology showed positive anti-leptospira IgM and negative anti-dengue IgM and IgG. Further, there was echocardiography suspected myocarditis due to high echogenicity in the left ventricle's basal-apical lateral endocardium. Thus, we diagnosed this case as leptospirosis with cardiac involvement. Direct cardiac tissue damage due to systemic vasculitis, disseminated intravascular coagulation, and pro-inflammatory cytokine storm is believed to be pathomechanism in leptospirosis with cardiac involvement. After diagnosis establishment, his final therapies in the hospital were Aspirin, Atorvastatin, Clopidogrel, Spironolactone, Ramipril, Carvedilol, Omeprazole, Doxycycline, and Ceftriaxone. Subsequently, he was discharged from hospital and continued to receive cardiovascular medications, antibiotics, antiplatelet, potassium-sparing diuretics, and omeprazole. Conclusion:Â This case highlights the importance of thorough clinical-laboratory evaluation in a patient with an atypical leptospiral presentation. Although Â leptospirosis is not a common cause of heart diseases such as STEMI, cardiogenic shock, and myocarditis, we recommend supportive therapy and correction of hemodynamic derangement for leptospirosis with cardiac involvement, in addition to leptospiral antibiotic drug itself.